SISTEMATIK REVIU TENTANG KECENDERUNGAN PERILAKU CYBERBULLYING DI KALANGAN REMAJA (SYSTEMATIC REVIEW OF THE TRENDS OF CYBERBULLYING BEHAVIOR IN ADOLESCENTS) - Dias Pandu Fisabilillah Fasya; Tri Na'imah (PSIMPHONI, 2021)
ABSTRACTCyberbullying is a behavior that can disturb others, this behavior almost occurs in adolescents aged 14-17 years The purpose of this systematic review is to synthesize trends in cyberbullying behavior among adolescent systematic reviews. This review was conducted by reviewing 26 articles from the Research Gate database source, SINTA, Sematic Scholar, DOAJ, Academia, CiterSeerX Google Scholar, Dergi Park, Springer. The author uses PICOSS (Population, Intervention, Comparators, Outcome Variables, Study Design and Setting) tables that are used to determine the inclusion, exclusion, detailed, clear and relevant criteria related to key components of the systematic review question. The findings of this study are that most of the trends in cyberbullying behavior from each journal can be synthesized into several cyberbullying behavioral tendencies such as spreading lies, sending messages or threats, imitating or acting on behalf of someone.Keywords :  Behavior, Cyberbullying Tendencies, Teenagers ABSTRAKCyberbullying merupakan perilaku yang dapat menganggu orang lain, perilaku tersebut hampir terjadi pada remaja umur 14-17 tahun. Tujuan dari sistematik review ini adalah mensintesakan kecenderungan perilaku cyberbullying di kalangan remaja sistematik review ini dilakukan dengan cara mereview 26 artikel yang berasal dari sumber database Research Gate, SINTA, Sematic Scholar, DOAJ, Academia, CiterSeerX Google Scholar, Dergi Park, Springer. Penulis menggunakan tabel PICOSS (Population, Intervention, Comparators, Outcome Variables, Study Design and Setting) yang digunakan untuk menentukan kriteria inklusi, eksklusi yang terperinci, jelas dan relevan berhubungan dengan komponen kunci dari pertanyaan peninjauan sistematis. Temuan dari penelitian ini adalah sebagian besar kecenderungan perilaku cyberbullying dari masing-masing jurnal dapat di sintesakan menjadi beberapa kecenderungan perilaku cyberbullying seperti menyebar kebohongan, mengirim pesan atau ancaman, meniru atau mengatasnamakan seseorang.Kata Kunci : Perilaku, Kecenderungan Cyberbullying, Remaja